(untitled) (Al-Academy, 2021)
The arts global digital marketing activity is one of the most prominent manifestations of the contemporary transformation in the circulation of cultural products, and that this event has become a new knowledge event that deserves to be a framework for the problem of our current research, while this phenomenon is growing and developing to compete with the traditional marketing of art through galleries, exhibitions, auctions and museums. It is still the preserve of certain civilized and knowledge environments, and from here this research comes with the aim of shedding light on the mechanisms of digitizing the contemporary art market that have been linked to the two variables of the growing idea of indirect marketing through the intermediary by companies, institutions or sites that specialize in marketing only, and the rapid development of the communicative digital world that has shaped Cybernetic support for marketing companies to benefit from the endless capabilities of linking all societal components with each other bypassing the restrictions of trade, sovereignty and privacy, so that these institutions have budgets that exceed the budgets of countries that are collected only through advertising, advertising, mediation, transportation and guaranteed delivery of products from the manufacturer to the consumer, and this has expanded The topic has become a comprehensive range of creative products, including the arts that have developed a deliberative circle And received it through that activity, and accordingly the search doors were designed - the first to show the websites of art marketing on the international information network, the second to define the technical requirements for the digital market and the third to read the reality of the digital market for art in the world, and that the theoretical limits of research are practically located on the sites of the World Wide Web of the Internet as of year 2000, the year of the practical beginning of art marketing and until the preparation of the research 2020, the research concludes with the illumination of this region, reveals its applied data, and invites contemporary Iraqi plastic art to participate in this club as an investment to distinguish plastic art in Iraq, as a technical product with international specifications. And to benefit from the widespread spread of digital communication mechanisms in Iraq, through the establishment of institutions and sites of connection for this system, because of the logical consequences of this in activating digital marketing for local contemporary arts in Iraq